Importance & Impact Of Guidance & Counseling Programme In The School Curriculum: A study conducted in public secondary schools of Kinondoni Municipality in Tanzania - Mwalukisa, Grace M.; Mwila, Prospery M. (Coution: Journal Counseling and Education, 2025)
This study aimed to contribute guidance and counselling approaches to character building among students in public secondary schools in Kinondoni Municipality, Tanzania. The study used a mixed research approach and a cross-sectional survey design. A sample size of 528, including secondary school teachers, students, heads of schools, and parents. From the findings, it is evident that 60% of the teachers employed dynamic interactions of a group of students’ approach, which aids in shaping and managing the behavior of students. Therefore, teachers tend to impose things on the students rather than making use of dialogue since they do not understand the environment created by students. The challenges recognized by the respondents were found to be the lack of separate counselling offices and necessary equipment, the absence of professionally trained guidance and counselling personnel, clear rules and guidelines and the lack of support from stakeholders. Last but not least, the study revealed that guidance and counselling are important to students and teachers; hence, they create a good relationship between students and teachers in school.